The challenge of time, memory and hope (Pontificia Universidad Católica de Chile. Facultad de Teología, 2007)
This article reflects upon the diverse dimensions and tensions of temporality: the time of human life is shown to be, at the same time, duration, projection and destination, and deepens in the moments of the projective line proper to events-that is, past-present-future. Then historicity is defined as that fundamental experience through which the human person, as a free subject, is found between a given past and a future yet to be created. The tensions involved are examined. Just by being as one is, the human person has to wait, and sees his or her existence as an inconclusive project, open to novelty. Human existence lives surrounded by possibility, and not only presence. For this reason, the article seeks to outline a criticism of the philosophies of progress that, upon failing to overcome an ontology of the present, lose their innovative force and damage their links with the past and the future. The idea is to rescue the past without disregarding the future. Only amamnetic reason, or memory, can save us from the forgetfulness of the past. Finally, the article proposes that Judeo-Christian faith values all time precisely because it believes in and awaits God, Creator and Consummate, the God of the living and the dead-in a word, the Lord of history and of all time.